Maintaining safety and efficacy for 3D printing in medicine - Christensen, Andy; Rybicki, Frank J. (3D printing in medicine, 2017)
Background The increased and accelerating utilization of 3D printing in medicine opens up questions regarding safety and efficacy in the use of medical models. The authors recognize an important shift towards point-of-care manufacturing for medical models in a hospital environment. This change, and the role of the radiologist as a central facilitator of these services, opens discussion about topics ranging from clinical uses to patient safety to regulatory implications. Results This project first defines three groups of patients for whom 3D printing positively impacts patient care. The steps needed for each group are described. Conclusions We provide our opinions regarding the regulatory role that we feel is most appropriate, balancing safety and efficacy with the autonomy of individuals in the field to make the greatest positive impact on healthcare.